Cancer cell death pathways caused by photothermal and photodynamic effects through gold nanoring induced surface plasmon resonance. (13th June 2017) - He, Yulu; Hsiao, Jen-Hung; Yu, Jian-He; Tseng, Po-Hao; Hua, Wei-Hsiang; Low, Meng-Chun; Tsai, Yu-Hsuan; Cai, Cheng-Jin; Hsieh, Cheng-Che; Kiang, Yean-Woei; Yang, C C; Zhang, Zhenxi
Abstract: The different death pathways of cancer cells under the conditions of the photothermal (PT), effect, photodynamic (PD) effect, and their combination are evaluated. By incubating cells with Au nanoring (NRI) either linked with the photosensitizer, AlPcS, or not, the illumination of a visible continuous laser for exciting the photosensitizer or an infrared femtosecond laser for exciting the localized surface plasmon resonance of Au NRI, leads to various PT and PD conditions for study. Three different staining dyes are used for identifying the cell areas of different damage conditions at different temporal points of observation. The cell death pathways and apoptotic evolution speeds under different cell treatment conditions are evaluated based on the calibration of the threshold laser fluences for causing early-apoptosis (EA) and necrosis (NE) or late-apoptosis (LA). It is found that with the PT effect only, strong cell NE is generated and the transition from EA into LA is faster than that caused by the PD effect when the EA stage is reached within 0.5 h after laser illumination. By combining the PT and PD effects, in the first few hours, the transition speed becomes lower, compared to the case of the PT effect only, when both Au NRIs internalized into cells and adsorbed on cell membrane exist. When the Au NRIs on cell membrane is removed, in the first few hours, the transition speed becomes higher, compared to the case of the PD effect only.